Intercrop Stylosanthes effects on millet yields and animal performance in the Sahel - Kouamé, C.; Hoefs, S.; Powell, J.M.; Roxas, D.; Renard, C. (International Livestock Centre for Africa, 1992)
The increasing interest in crop-livestock integration in sub-Saharan Africa has emphasised the beneficial uses of forage legumes in cereal-based cropping systems. Forage legume-cereal cropping systems were evaluated in 1989 and 1990 at the ICRISAT (International Crops Research Institute for the Semi-Arid Tropics) Sahelian Center along with the performance of sheep fed millet residues as a basal diet and supplemented with forage legume hay. Intercropping Stylosanthes fruticosa (Retz.) Alston and S. hamata (L.) Taub. with millet (Pennisetum glaucum (L)R.Br) did not significantly affect grain yields during the legume establishment year. During the second year, when millet was planted into pre-established Stylos, total biomass and crude-protein yields increased by 45 and 125 percent, respectively, yet millet grain yield decreased by more than 30 percent. Sheep supplemented with 500 g Stylos hay per day consistently gained weight during 60-70 day pen-feeding and grazing trials. Management strategies are needed to fully exploit the agronomic benefits and feeding value of forage legumes introduced into Sahelian mixed farming systems.